2022
DOI: 10.1002/jcph.2033
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Analysis and Dosing Optimization of Sirolimus in Children With Tuberous Sclerosis Complex

Abstract: Sirolimus is confirmed to be effective in the treatment of tuberous sclerosis complex (TSC) and related disorders. The study aims to establish a population pharmacokinetic model of oral sirolimus for children with TSC and provide an evidence‐based approach for individualization of sirolimus dosing in the pediatric population. A total of 64 children were recruited in this multicenter, retrospective pharmacokinetic study. Whole‐blood concentrations of sirolimus, demographic, and clinical information were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Ni et al reported population pharmacokinetics of ciclosporin in Chinese children with aplastic anemia: effects of weight, renal function, and stanozolol administration, the Ka of ciclosporin was fixed at 0.68/h ( Ni et al, 2013 ). Li et al reported population pharmacokinetic analysis and dosing optimization of sirolimus in children with tuberous sclerosis complex; the Ka of sirolimus was fixed at 0.7521/h ( Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ni et al reported population pharmacokinetics of ciclosporin in Chinese children with aplastic anemia: effects of weight, renal function, and stanozolol administration, the Ka of ciclosporin was fixed at 0.68/h ( Ni et al, 2013 ). Li et al reported population pharmacokinetic analysis and dosing optimization of sirolimus in children with tuberous sclerosis complex; the Ka of sirolimus was fixed at 0.7521/h ( Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%